REGARDING THE FORMATION OF DIVERGENT THINKING OF CHILDREN OF PRESCHOOL AGE THROUGH PLAY - Shokirjonova Fotimakhon Murodjon kizi. (Western European Studies, 2024)
This article discusses the formation of divergent thinking of preschoolers through play.
Keywords: Divergent thinking; meditation; improvisation; stereotypical thinking